The barriers to the implementation of e-tendering systems among contractors - Nazri, Muhammad Amirun (2024)
The e-tendering platform has brought about a significant transformation in the construction industry, specifically among G7 companies in Pulau Pinang. Nevertheless, the transition away from conventional tendering methods, which heavily depend on manual processes and physical documentation, has faced substantial barriers. The barriers encompass resistance to change, inadequate technological infrastructure, security apprehensions, and the necessity for standardization and regulatory adherence. The objective of this research is to identify the impact of implementation of e tendering system, to investigate the barrier in implementation of e-tendering system and to propose the most effective solution to enhance the e-tendering system. The study examines the current status of e-tendering in the construction industry by conducting a thorough review of literature and empirical research. It focuses on the barriers that contractors encounter and proposes effective solutions to these issues. The results indicate that the effective implementation of e-tendering systems depends on comprehensive training, rigorous testing, and robust support from senior management and local government. This study not only enhances our comprehension of e-tendering in Malaysia but also offers practical suggestions for industry stakeholders, policymakers, and academics. As a result, it promotes the successful implementation of e-tendering systems in the construction sector.